The Organizational Climate and its Relationship to the Professional Growth of Female Teachers in Private Schools in the State of Kuwait - Hanan Nasser Al-Adwani (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: The current study aims to investigate the relationship between the level of professional development of female teachers in Kuwaiti private schools and the level of implementation of organizational climate dimensions (organizational structure, administrative leadership, incentive system, participation in decision-making, training and development). Methods: The descriptive survey approach was used. The questionnaire was given to a sample of (125) female teachers working in private schools in Kuwait as a means of gathering the primary data. Results: According to the study, female teachers in private schools in the State of Kuwait were highly engaged in the organizational climate's components (organizational structure, administrative leadership, incentive system, participation in decision-making, training and development). Female teachers in private schools in the State of Kuwait experienced a significant degree of professional progress. At Kuwaiti private schools, the study discovered a positive relationship between organizational climate traits and female teachers' professional development, with statistical significance at the level of 0.05. Also, it was shown that there are statistically significant differences between the responses of the study sample due to the educational level and teaching experience factors and their interactions, favoring those with a bachelor's degree and more than 11 years of experience. Conclusions: The study came to the conclusion that there is a favorable association between the organizational climate characteristics and the professional development of female teachers in Kuwaiti private schools. According to the study, systems of financial and moral incentives should be strengthened, and all female teachers should receive financial and moral incentives.